Ending(s), Seriality And Interdiscursivity - Elsa Lorphelin Blaise (Sillages Critiques)
This article examines the issue of the collection of short-stories in the works of Jean Rhys and Janet Frame. Within its composition itself, it stages the necessary yet paradoxical repetition of endings, along with the incessant regeneration and reinstatement of the narrative voice. Far from being a self-sufficient literary production anymore (according to E.A. Poe’s theories for instance), the short-story discusses and re-evaluates the notion of ending, but also elaborates upon the rejection of one final ending inside the collection, thus creating effects of echo, repetition and intertextuality. Thus dismissing the hermetical qualities of the short-story, the collection becomes the place where voices interact, just as it destabilises one of the essential markers of the genre: the strength of the dénouement, and the notion of closure that follows from it.